ANALISIS PENGARUH KALOR TERHADAP MUTU KOPI PADA PENGGUNAAN ALAT PENGERING HYBRID KOPI - Aurellya Abdillah Wijaya Putri; Firda Shahira; Tia Dwi Riskiyanti; Sudarti Sudarti; Trapsilo Prihandono (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2023)
Coffee is one of the plantation products that is highly recommended to be developed because it is able to become a source of state income and improve the economy where almost half a million Indonesians are entrepreneurs and coffee farmers. Heat is the process of transferring energy from a substance to another substance due to temperature differences. During this time, the coffee drying process is done in the traditional way. This drying process is not optimal because the temperature cannot be controlled properly, which affects the quality of the coffee. During rainy conditions, coffee is dried for a long time so that mold can occur. However, temperatures that are too high can also have a negative impact on coffee quality, especially on coffee aroma. The solution that can be done is to use a hybrid coffee drying machine. This study aims to analyze the effect of heat on the quality of coffee which in its production uses a hybrid coffee dryer. This research was conducted using the literature study method or literature study. The results showed that heat plays an important role in the quality of coffee quality in a hybrid coffee dryer. The quality of coffee depends on the temperature of the machine. The hybrid coffee drying machine is automatically designed where the temperature in the drying chamber is constant at the minimum temperature.